Risk of strong antibody decline in dialysis and transplant patients after SARS-CoV-2mRNA vaccination: Six months data from the observational Dia-Vacc study - Julian Stumpf; Jörg Schwöbel; Tom Lindner; Leona Anders; Torsten Siepmann; Claudia Karger; Jan Hüther; Heike Martin; Petra Müller; Robert Faulhaber-Walter; Torsten Langer; Holger Schirutschke; et al. (The Lancet Regional Health. Europe, 2022)
Summary: Background: Vulnerable dialysis and kidney transplant patients show impaired seroconversion rates compared to medical personnel eight weeks after SARS-CoV-2mRNA vaccination. Methods: We evaluated six months follow up data in our observational Dia-Vacc study exploring specific cellular (interferon-γ release assay) or/and humoral immune responses after 2x SARS-CoV-2mRNA vaccination in 1205 participants including medical personnel (125 MP), dialysis patients (970 DP) and kidney transplant recipients (110 KTR) with seroconversion (de novo IgA or IgG antibody positivity by ELISA) after eight weeks. Findings: Six months after vaccination, seroconversion remained positive in 98% of MP, but 91%/87% of DP/KTR (p = 0·005), respectively. Receptor binding domain-IgG (RBD-IgG) antibodies were positive in 98% of MP, but only 68%/57% of DP/KTR (p < 0·001), respectively. Compared to MP, DP and KTR were at risk for a strong IgG or RBD-IgG decline (p < 0·001). Within the DP but not KTR group male gender, peritoneal dialysis, short time on dialysis, BNT162b2mRNA vaccine, immunosuppressive drug use and diabetes mellitus were independent risk factors for a strong decline of IgG or RBD antibodies. The percentage of cellular immunity decline was similar in all groups. Interpretation: Both vulnerable DP and KTR groups are at risk for a strong decline for IgG and RBD antibodies. In KTR, antibody titres peak at a markedly lower level and accelerated antibody decline is mixed with a delayed/increasing IgG, RBD-IgG, or cellular immune response in a 16% fraction of patients. In both populations, immune monitoring should be used for early timing of additional booster vaccinations. Funding: This study was funded by the Else Kröner Fresenius Stiftung, Bad Homburg v. d. H., grant number Fördervertrag EKFS 2021_EKSE.27.